2019
DOI: 10.1103/physrevb.99.134518
|View full text |Cite|
|
Sign up to set email alerts
|

Comprehensive Eliashberg analysis of microwave conductivity and penetration depth of K-, Co-, and P-substituted BaFe2As2

Abstract: We report on the combined experimental and theoretical analysis of microwave-frequency electromagnetic response of BaFe2As2 single crystals with different substitutions: K in the site of Ba (hole doping), Co in the Fe site (electron doping) and P in the As site (isovalent substitution). Measurements by a coplanar resonator technique lead to the experimental determination of the penetration depth and microwave conductivity as a function of temperature. The whole set of data is analyzed within a self-consistent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 71 publications
2
35
0
Order By: Relevance
“…The Eliashberg theory has been proven very helpful in the interpretation of experimental data for IBSs due to the possibility of taking into account the spin-fluctuation pairing mechanism and the multiband nature of these materials [24,25]. The London penetration depth can easily be calculated from the solution of the imaginary-axis version of the Eliashberg equations.…”
Section: E Eliashberg Modellingmentioning
confidence: 99%
“…The Eliashberg theory has been proven very helpful in the interpretation of experimental data for IBSs due to the possibility of taking into account the spin-fluctuation pairing mechanism and the multiband nature of these materials [24,25]. The London penetration depth can easily be calculated from the solution of the imaginary-axis version of the Eliashberg equations.…”
Section: E Eliashberg Modellingmentioning
confidence: 99%
“…In particular, it has been shown that magnetic moments in the FeAs layers of iron-based pnictides have a tendency to order antiferromagnetically and it has been theorized that AFM spin fluctuations can induce the s ± pairing at the origin of superconductivity in these compounds [1]. This picture, although not completely accepted, has been suggested for several compounds of the so-called 122 family, i.e., BaFe 2 As 2 with various substitutions, isovalent or inducing electron or hole doping [2][3][4]. Within this framework, systems also containing magnetic rare-earth-metal elements are of interest, since at low temperatures they develop additional magnetic ordering of local moments.…”
Section: Introductionmentioning
confidence: 99%
“…The complete characterization of the London penetration depth (absolute value and temperature dependence) can also be carried out by means of a microwave resonator (MWR) technique that has already been applied to other IBS crystals [20][21][22]28,29]. In this case the measurement system consists of an YBa 2 Cu 3 O 7−x coplanar waveguide resonator (with resonance frequency f 0 of about 8 GHz) to which the sample is coupled.…”
Section: Microwave Resonatormentioning
confidence: 99%
“…In the IBS it has been shown that electron-boson coupling is mainly provided by antiferromagnetic spin fluctuations [11], therefore we neglect the phononic contribution and we consider the shape of the spectral functions α 2 i j F sf ( ) discussed in detail in Refs. [20,28]. However, since the two-band model is an effective one, it is not possible to set to zero the intraband coupling, hence the resulting electron-boson coupling-constant matrix .…”
Section: E Eliashberg Modelingmentioning
confidence: 99%
See 1 more Smart Citation